The Use of Indirect Calorimetry for Nutrition Assessments in Patients with Chronic Inflammatory Gastrointestinal Conditions - Fardowsa, Abdi (My University, 2023)
Resting energy expenditure (REE) is challenging to predict in chronic inflammatory gastrointestinal conditions (CIGI) such as celiac disease (CeD) and inflammatory bowel disease (IBD). In clinical practice, predictive equations (PE) are often used to provide estimates of REE. However, indirect calorimetry is a gold-standard method for accurate measurement of energy needs. The central hypothesis for this study was that there would be differences in predicted and measured energy needs in CIGI. We conducted a prospective observational study at an outpatient clinic where REE (kcal/day) was measured by the Q-NRG® Metabolic Cart. This was compared with REE estimated by five commonly used PE (25 kcal/kg, Harris-Benedict, Schofield, Mifflin-St. Jeor and Owen) using paired t-tests (IBM SPSS Version 29.0). REE (kcal/day) and REE adjusted for weight (REE/kcal/kg) were compared in different GI groups using Mann-Whitney U tests. The study population comprised eighty-seven patients with CIGI (CeD [n=61], IBD [n=10], and Other [n=16]). Mean REE (1462 ± 281) was significantly lower compared with several PE: 1) 25 kcal/kg (1933 ± 536; p <0.001); 2) Harris-Benedict (1552 ± 287; p<0.001); 3) Schofield (1522 ± 282, p=0.01), while higher than Owen (1411 ± 228, p=0.02) and similar to Mifflin St. Jeor (1450 ± 277; p=0.56). REE adjusted for weight (kcal/kg/day) was significantly higher in IBD as compared with CeD patients (22.9 vs 18.2; p=0.04), potentially due to differences in disease activity (16% CeD with active disease vs. 60% IBD with active disease; p=0.0022). Furthermore, fat-free mass (FFM) (r=0.70, p<0.001), BMI (r=0.47, p<0.01), and protein intake (r=0.24, p=0.02) were important predictors of REE in this cohort. The present results suggest that basal caloric needs are inaccurately predicted by PE, which may have significant implications in the long-term nutritional management of CeD and IBD.